Element Specific Atom Counting at the Atomic Scale by Combining High Angle Annular Dark Field Scanning Transmission Electron Microscopy and Energy Dispersive X‐ray Spectroscopy. Issue 11 (30th September 2022) - De Backer, Annick; Zhang, Zezhong; van den Bos, Karel H.W.; Bladt, Eva; Sánchez‐Iglesias, Ana; Liz‐Marzán, Luis M.; Nellist, Peter D.; Bals, Sara; Van Aert, Sandra
Abstract: A new methodology is presented to count the number of atoms in multimetallic nanocrystals by combining energy dispersive X‐ray spectroscopy (EDX) and high angle annular dark field scanning transmission electron microscopy (HAADF STEM). For this purpose, the existence of a linear relationship between the incoherent HAADF STEM and EDX images is exploited. Next to the number of atoms for each element in the atomic columns, the method also allows quantification of the error in the obtained number of atoms, which is of importance given the noisy nature of the acquired EDX signals. Using experimental images of an Au@Ag core–shell nanorod, it is demonstrated that 3D structural information can be extracted at the atomic scale. Furthermore, simulated data of an Au@Pt core–shell nanorod show the prospect to characterize heterogeneous nanostructures with adjacent atomic numbers. Abstract : The linear scaling between energy dispersive X‐ray imaging and high angle annular dark field scanning transmission electron microscopy image intensities is explicitly used to count the number of atoms in heterogenous nanocrystals. Considering that this novel methodology can be applied even when elements have almost identical atomic numbers, it opens up new opportunities to study atom‐by‐atom the structure of a wide variety of multimetallic nanocrystals.